2021
DOI: 10.1007/s12539-021-00475-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Protein–Protein Interaction Networks and Somatic Mutation Data to Detect Driver Modules in Pan-Cancer

Abstract: Background: With the constant update of large-scale sequencing data and the continuous improvement of cancer genomics data such as the cancer genome atlas ICGC and TCGA, it gains increasing importance how to detect the functional high-frequency mutation gene set in cells that causes cancer within the field of medicine.Methods: In this study, to solve the issue of mutated gene heterogeneity and improve the accuracy of driver modules, we propose a new recognition method of driver modules, named ECSWalk, based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The results of applying the MCODE, ClusterONE, HC‐PIN, OH‐PIN and NetAP methods to prostate cancer data from TCGA are shown in Table 4 , where the effective modules are driver modules with p ‐value<0.05 and the module size is ≥ 3 [ 27 , 28 ]. It can be seen from Table 4 that both the HC‐PIN and NetAP methods identify more candidate driver genes than the other three methods, which indicates that the HC‐PIN and NetAP methods have a better ability to capture driver genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of applying the MCODE, ClusterONE, HC‐PIN, OH‐PIN and NetAP methods to prostate cancer data from TCGA are shown in Table 4 , where the effective modules are driver modules with p ‐value<0.05 and the module size is ≥ 3 [ 27 , 28 ]. It can be seen from Table 4 that both the HC‐PIN and NetAP methods identify more candidate driver genes than the other three methods, which indicates that the HC‐PIN and NetAP methods have a better ability to capture driver genes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the driver modules have two key characteristics, namely high coverage and high mutual exclusivity [ 14 ], which have been widely used in carcinogenic driver module identification [ 25 , 26 , 27 , 28 ]. The definitions of coverage and mutual exclusivity are described in this section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, while MVKTS currently concatenates features extracted by various methods, integrating advanced gene feature fusion techniques to combine four types of omics data could potentially enhance the identification of pan-cancer driver genes [33][34][35]. The application of weighted fusion can also be considered to further improve the performance of MVKTS [36,37].…”
Section: Discussionmentioning
confidence: 99%